OBSERVATIONS ON THE LARVAE AND JUVENILES OF THE ’BHEKTI’, LATES CALCAJUFER (BLOCH) FROM THE HOOGHLY-MATLAH ESTUARINE SYSTEM - Ghosh, Apurba (Indian Journal of Fisheries, 2011)
The cultivation of carnivorous fishes is a new trend in flsh culture practice throughoutthe world. Among such speciesLa^e; ca/car(/erXBIoch)is considered to be one of the most important in view of its excellent quality as a table fish. Investigations on the seed resources of these species is an essential pre-requisite for assessing the cultural possibilities. In the present communication an attempt is made to describe the characters of larvae andjuvenilesof L.c<jfcflr//er between 6 and 69mm length which would be useful aids for identification, especially under field conditions. Information collected on the distribution of L(ire5 Seed in the Hooghly-Matlah estuarine system is also incorporated. The availability of the seed in significant numbers at Kulpi, Rajnagar and Shyanmagar, (24-Parganas West Bengal) during the pre-monsoon months has been highlighted.